The modern paradigm of rational environmental use as a trend of environmental legal regulation (Nexo Revista Científica, 2021)
The main aim of the article is to review modern concepts of the legal principle of rational nature management. To fulfil that aim, a descriptive-analytical and data-gathering methods are utilized. The principle of rational environmental management should be considered as a modern paradigm of environmental and legal regulation. The article substantiates that this paradigm includes doctrinal views on the legal support of rational use of natural resources, state environmental policy, a set of existing legal norms on rational use of natural resources, legal relations on the use of natural resources, and a developed ecological culture. The authors concluded that the central core and an obvious trend in the environmental management paradigm is the idea of the best available technologies.